"Staying with the trouble" of response-able Spanish bilingualism: a diffractive inquiry. Issue 4 (2nd October 2021) - Heinrichs, Danielle H.
ABSTRACT: This analysis is but one small fragment of a broader project exploring conceptions of response-able Spanish bilingualism in Australian secondary education. An initial thematic analysis revealed patterns and trends in the data but overlooked the nuanced, subtle differences regarding the ways in which Spanish bilingualism might be entangled with a number of troubling discourses and practices. Drawing inspiration from concepts in decolonial, new material, and sociolinguistic theories, I explore how a diffractive inquiry of my conversations with Spanish as a world language teachers (SWLTs) might attend to the affirmative differences and transgressive data they mention. Through this diffractive inquiry of focus group conversations with SWLTs in Australia, a multitude of response-abilities emerged relating to digital antagonisms in and beyond the classroom, the role of experimental practices in supporting Spanish and other named languages and the capacity for us as researchers to remain mindfully attentive to the generative affects present in this type of data. Hence, such an inquiry presents an opportunity to focus on previously unseen data but also invites all those engaging in critical language inquiries to question their response-abilities as researcher/teacher/learners.